The Behavioral Response of Komodo Dragons (Va- ranus komodoensis OUWENS, 1912) During Mating and Nesting Periods towards Tourist Presence in Loh Buaya, Komodo National Park - Aditya Dimas Pramudya; Achmad Sjarmidi (School of Life Sciences and Technology, Institut Teknologi Bandung, 2023)
It has been recognized in many studies that wildlife tourism practices might generate a negative impact on wildlife, particularly during the reproductive period. Some wildlife may lower their sensitivity towards tourist presence, for instance in Komodo. Understanding to what extenthabituation occurs in Komodo would be necessary for tourism management in Komodo National Park (KNP). Therefore, this study aimed to identify the response of Komodo to tourist presence during mating and nesting activities. The observation was conducted in Loh Buaya, which is one of the tourism sites in KNP. Komodo’s responses were divided into (1) avoidance; (2) neutral; and (3) aggressive under categorized stimulus: tourist number (i.e., < 5 persons; 5-10 persons; and > 10 persons) and distance (i.e., < 5 m; 5-10 m; and > 10 m). Correlation analysis was performed to identify any influences on mating and nesting activities. Our results revealed that Komodo inhabiting tourism facilities havebeen habituated to tourist presence. Different tourist frequencies did not influence Komodo mating activities (r(20)= 0.036, p=0.873), the nest preparing activity (i.e., digging proportion; r(22)= 0.054, p=0.803) and the guarding activity (i.e., nesting proportion; r(22)= 0.314, p=0.135).Nevertheless, our results indicated possible impacts due to tourism activities and its supporting facilities, such as dominated mating pairs, threats to female reproductive success, and human-Komodo conflicts. Therefore, habituation evi- dence must be carefully considered in order todevelop more corresponding strategies and achieve sustainable tourism practices.